Back to work: Re-employment, earnings and skill use after job displacement - OECD (OECD Publishing, 2013)
This report provides new and more extensive evidence of job displacement and its consequences for 14 countries. Job displacement, i.e. involuntary job loss due to economic factors such as economic downturns or structural change, is highly cyclical but has not exhibited any upwards trend over the past decade.
Keywords: Employment -- Exit from employment (Retirement/Redundancy); Income & Finance -- Income (Salary and Wages); Employment -- Labour force participation; Ageing; Income, wealth and finances; Labour market; Employment; Income & Finance; Labour force participation; Exit from employment (Retirement/Redundancy); Income (Salary and Wages); Income, wealth and finances; Ageing; Employment and unemployment